Efficacy of Tenofovir in Patients with Lamivudine Failure Is Not Different from That in Nucleoside/Nucleotide Analogue-Naïve Patients with Chronic Hepatitis B - Baran, Bulent (American Society for Microbiology, 2013)
We evaluated the efficacy of tenofovir disoproxil fumarate (TDF) in patients with lamivudine failure (LAM-F) in comparison with that in nucleoside/nucleotide analogue (NA)-naïve patients with chronic hepatitis B (CHB). The criteria for inclusion were being NA naïve or having previous LAM-F and receiving TDF therapy for at least 6 months. Biochemical and virological tests were performed at the baseline, at 3-month intervals in the first year, and every 6 months thereafter. The primary outcome measure for efficacy was a complete virological response (CVR), defined as an HBV DNA level of <20 IU/ml. CVR rates were calculated by Kaplan-Meier analysis, and a multivariate Cox proportional-hazard model was generated in order to find predictive factors independently associated with the time to a CVR. We included 197 patients in the study (136 males; mean age, 43 ± 12 years; 105 patients were NA naïve). Sixty-five patients had hepatitis B e antigen (HBeAg)-positive CHB. The median duration of TDF treatment was 29 (range, 6 to 52) months. Seventy-one patients (77%) in the LAM-F group were treated with TDF add-on therapy. The CVR rates of the NA-naïve and LAM-F groups were comparable in HBeAg-negative (94% versus 96% at month 36, P = 0.10) and HBeAg-positive patients (67% versus 83% at month 36, P = 0.48). According to the multivariate Cox regression model, only HBeAg positivity (hazard ratio [HR], 0.39; 95% confidence interval [CI], 0.26 to 0.59; P < 0.001) and a high baseline HBV DNA level (HR, 0.44; 95% CI, 0.29 to 0.67; P < 0.001) had a significant influence on the time to a CVR. The similar cumulative CVR rates during the follow-up show that TDF has comparable efficacy in lamivudine-experienced and NA-naïve patients, and the presence of resistance mutations did not alter the response rates.